Implementasi Restful Web Service pada Aplikasi Surat Keterangan Pendamping Ijazah (SKPI) Berbasis Web - Retnowati, Sri; Nugroho, Ditya Dwi (Jurnal Kridatama Sains dan Teknologi, 2024)
In current technological developments, many human jobs have been replaced by machines, and the most widely used currently are computers. Computer technology has now entered all aspects of life, especially in the field of education. Currently, the teaching and learning process is greatly influenced by technological developments. The system that will be developed is in the form of a website with RESTFUL web service technology. The development method used in this research is the waterfall method which consists of four development stages, namely: (1) Analysis, (2) Design, (3) Coding, and (4) Testing. After this system has been created, black box testing and trials are carried out on potential users of the system to see the suitability of the system. Based on the research results, it is stated that the application for making a Diploma Companion Certificate (SKPI) can shorten the time and is more efficient compared to the previous procedure which still used manual or semi-manual methods. Apart from that, based on the results of black box testing and trials by potential users, it show that the system is running well and as expected. Thus it can be said that this system is feasible to implement.